Organizational Culture Management and Job-Satisfaction As Teacher Job-Performance Predictors - Wesly Hutabarat (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: This study is a causal research which is intended to find out direct and indirect effects of organizational culture and job-satisfaction on job-performance. As many as 143 of 645 public high school teachers were selected from 10 pulic high schools in Medan, Indonesia by stratified random sampling techniques. The classroom teacher samples selected were teachers who have teaching experiences for at least 10 years, and have been certified as professional teachers and received certification fees continuously, except for guidance and counseling teachers. It was found that the direct effect of Organizational Culture on Job Satisfaction is 32.50%, while the direct effect of Job Satisfaction and Organizational Culture on Performance is 16.70% and 35.60% respecively. The indirect effect of Organizational Culture on Performance through Job Satisfaction is 14.50%. So the total effect of Organization Culture on Performance is 33.3%. Based on the findings, it can be concluded that organizational culture, organizational structure and job satisfaction have a positive impact on the teacher job-performance of high school teachers in Medan.Keywords: Job-Performance, Job-Satisfaction, Organizational Culture